Influence of parasitism on the use of small terrestrial rodents in environmental pollution monitoring - Jankovská, Ivana; Miholová, Daniela; Langrová, Iva; Bejcek, Vladimír; Vadlejch, Jaroslav; Kolihová, Dana; Sulc, Miloslav (Environmental pollution (Barking, Essex, 2009)
Bioaccumulation of cadmium, chromium, copper, manganese, nickel, lead and zinc in small terrestrial rodents - voles and their cestode parasite Paranoplocephala dentata was studied. Contents of Pb, Mn, Ni and Zn in the parasite were found to be higher than in the kidney and liver of the parasitized animals. Lead level in the cestode was 37 fold higher than in the liver of the infected rodents. Bioaccumulation factors of zinc, nickel and manganese in the cestode are mostly in the range from 2 to 4.5. Considering the different contents of manganese and zinc in livers of non-parasitized and parasitized rodents, kidney tissue was found to be more reliable than liver as an indicator of environmental pollution by manganese and zinc; the kidneys of parasitized animals showed no significant change in the concentrations of those elements that are accumulated in the cestode.
Keywords: znečištění životního prostředí; Environmental Pollutants; Stress, Physiological; látky znečišťující životní prostředí; monitorování životního prostředí; Environmental Monitoring; Environmental Pollution; Metals, Heavy; cestodózy; zvířata; Cestode Infections; fyziologický stres; Arvicolinae; těžké kovy; Animals